Clinical characteristics, risk factors and angiographic profile of acute coronary syndrome patients in a tertiary care center of Nepal. - Shakya, Abhishesh; Jha, Sunil Chandra; Gajurel, Ratna Mani; Poudel, Chandra Mani; Sahi, Ravi; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev (Nepalese Heart Journal, 2019)
Background and Aims: Acute coronary syndrome (ACS) refers to a group of clinical symptoms consistent with new onset or worsening ischemic symptoms. ST-elevation myocardial infarction (STEMI), non-ST elevation myocardial infarction (NSTEMI) and unstable angina (UA) are the three types of ACS. The objectives were to study the risk factors prevalence, angiographic distribution and severity of coronary artery stenosis in ACS among patients admitted in Cardiology Department of Manmohan Cardiothoracic Vascular and Transplant Center (MCVTC). Methods: This is a restrospective study of 419 ACS patients admitted and treated in MCVTC from November 2017 to October 2018. Patients were divided into STEMI, NSTEMI and UA then analyzed for various risk factors, angiographic patterns and severity of coronary artery disease. Results: Mean age of presentation was 59.3Å}12.8 years. Majority were male 317(75.7%). Most patients had STEMI 252 (60.1%) followed by NSTEMI 98 (23.4%) and UA 69 (16.5 %). Risk factors: smoking was present in 241 (57.5%), hypertension in 212 (50.6%), diabetes in 144 (34.4%), dyslipidemia in 58 (13.8%). Single-vessel disease was present in 34.6 % patients, double- vessel disease was present in 27.44 % patients and triple vessel disease was present in 26.3 % patients, left main disease in 1.4 % patients. Normal coronaries were present in 6.4% patients and minor coronary artery disease in 3.8 % patients. Conclusions: STEMI was the most common presentation. Three quarters of ACS were male patients. Smoking was most prevalent risk factor. Single vessel involvement was the most common CAG finding in all spectrum of ACS. Diabetic patients had more multivessel disease.